Penentuan Harga Jual Biji Jarak Kering Dengan Metode Activity Based Cost System Untuk Mendukung Pertanian Berkelanjutan: Studi Kasus Nusa Penida, Bali - Kurniawan, Radha; Hartati, Rukmi Sari; Kumara, I N Satya (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi Elektro, 2019)
The aim of this research was to determine  the price of jatropha seed at farmer level in Nusa Penida island, Bali, where the location was highly potential for Jatropha seed development as the main raw material of biodiesel production. The biodiesel price wass calculated using Activity-Based Cost System method. This method calculated biodiesel’s prices more accurate because it took a detailed activities costing in the biodiesel processing. The activities consisted of the production process activities at the unit and batch levels, where the costs were grouped by activity type according to Activity-Based Cost System, then grouped again into activity cost pool. It was found that the biodiesel price was Rp. 4,076.25 per liter which was higher than the current price of Rp. 3,893.9 per liter. The calculated biodiesel prices was then calibrated against with the price of industrial diesel oil in Nusa Penida island further calculation was carried out to determine  the price of dried Jathropha seeds.